Experience of urban forest management in Latvia from the perspective of experts and sites’ managers - Kraukle, Ieva; Jūrmalis, Edgars; Stokmane, Ilze; Vugule, Kristīne (Landscape Architecture and Art, 2024)
With the expansion of urbanization, urban structures are changing. In recent decades, increasing attention has been paid to the maintenance and expansion of green spaces. Urban forests, as highly natural multifunctional structures, effectively meet human needs for environmental and social ecosystem services while requiring significantly fewer resources for maintenance compared to parks and landscaped areas. Latvia is rich in forests that have been historically preserved in urban and suburban areas. To assess the management situation of urban forests, six cities rich in urban forests were selected: Riga, Jurmala, Daugavpils, Jelgava, Liepaja, and Ogre. According to European experience, urban forest management is characterized by integration, long-term management strategies, multidisciplinary approaches that go beyond forestry activities, and the involvement of various stakeholders. The authors propose a definition of urban forests specific to Latvia and outline their main functions—social, environmental, educational, nature conservation, aesthetic, and economic. In addition, key challenges and problems were identified based on the opinions of ten experts in urban forest management. The aim of this article is to evaluate approaches to urban forest management in Latvia and to provide recommendations for improving urban forest management. Field studies of forest areas in six cities were conducted, meetings with experts were held, available statistical data on forest areas were analyzed, and municipal and management company strategies, forest management plans, and other relevant information were reviewed. The study compiled and analyzed urban forest areas, their distribution within cities, specially protected areas, forest parks, dominant tree species, forest landscape characteristics, and the potential of natural resources for recreation Recommendations were made: to develop an understanding of urban forest functions, to define and identify areas critical to these functions, and to recognize them in the field. Urban forest managers should consider a wide range of knowledge, not limited to forestry, encourage collaboration between stakeholders, and educate the public. It is important to improve recreational areas, implement zoning of maintenance intensity to reduce anthropogenic pressure, ensure accessibility, preserve natural values, and enhance resilience to climate change. It is also essential to update legislation on urban forest management to reflect current conditions.